Sustainable and Balanced Energy Efficiency and Preservation in Our Built Heritage - Heidi Norrström (Sustainability, 2013)
Today, conservation work in our built cultural heritage has to be reformulated due to the new energy efficiency requirements put forward. On both a national and an international level, energy efficiency measures are considered key actions within sustainability work, answering to the global issue of climate change. What does this imply for our built heritage? Contemporary conservation is characterized by the concept of sustainability, and integrated conservation is also expected to be sustainable. It is inherent in this tradition, but how are we going to balance the historic and architectural values with the new energy requirements? A research project, Energy Efficiency in Our Cultural Heritage (EEPOCH), consisting of a multiple case study, has been carried out over three years, studying selected objects restored within the Halland Model, a project over a decade long. In EEPOCH the multiple units of analysis are energy efficiency, historic and architectural values, management, and legislation. All are applied to the selected objects. The results and conclusions drawn from the analysis show that there are actions that are possible to take and to recommend, including national inventories of historic values in the existing building stock as well as guidance for the management of historic values on a municipal level for continued sustainable development.